A study on the maneuverability of a twin-screw LNGC under machinery failure. (1st May 2018) - You, Youngjun
Abstract: Ship owners and classification societies have recently begun to require assessments of the maneuverability of twin-screw ships under machinery failure. Since such an assessment has not yet been previously conducted, its concept and process have not been clearly established. In this paper, we construct a simulation that predicts the maneuverability of a ship under machinery failure and propose a process to conduct IMO maneuvering tests under machinery failure, and this is referred to as single propeller failure, single rudder failure, aligned combination failure, and cross combination failure. A mathematical model for the simulation under normal operating condition is verified, and assumptions are applied to the existing mathematical model to introduce machinery failure. The suggested procedure is followed to verify a mathematical model with these assumptions under machinery failure by conducting sea trials. Finally, numerical simulations for mandatory tests are conducted for the defined failures, and the physical characteristics of each failure are investigated compared to those under normal operating conditions. Highlights: To suggest a IMO maneuvering test procedure under machinery failures. To suggest a simulation method based on a mathematical model verified under normal operating conditions. To investigate unique characteristics due to failures based on the simulated IMO maneuvering tests under machinery failures.